2010
DOI: 10.1136/sti.2009.038737
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour and sexual health of young international travellers (backpackers) in Australia

Abstract: Backpackers should be a priority population for sexual health promotion and access to services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 15 publications
3
32
1
Order By: Relevance
“…This study of travellers in Hong Kong is quite similar to the current study in terms of the population characteristics and the primary findings, which are largely consistent with our results. However, another crosssectional study conducted with travellers (backpackers) in Australia reported a frequency of inconsistent condom use of 78%, which is higher than that observed in the present study [21]. In contrast, a cross-sectional study of a sample of 45 travellers returning from tropical destinations reported that none of the participants practised consistent condom use (40% confirmed irregular use, and 60% never used condoms).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…This study of travellers in Hong Kong is quite similar to the current study in terms of the population characteristics and the primary findings, which are largely consistent with our results. However, another crosssectional study conducted with travellers (backpackers) in Australia reported a frequency of inconsistent condom use of 78%, which is higher than that observed in the present study [21]. In contrast, a cross-sectional study of a sample of 45 travellers returning from tropical destinations reported that none of the participants practised consistent condom use (40% confirmed irregular use, and 60% never used condoms).…”
Section: Discussioncontrasting
confidence: 97%
“…First, because this is a cross-sectional study, it cannot be used to establish causal relationships. However, our results are similar to those of other cross-sectional studies with larger sample sizes [19,21]. We recommend conducting additional studies in the future to evaluate other factors, such as the intrinsic sexual behaviour of each individual.…”
Section: Limitationssupporting
confidence: 89%
See 1 more Smart Citation
“…The higher prevalence in regional or rural areas could be a reflection of less access to health services 23. Aboriginal and Torres Strait Islander people are known to be at higher risk of chlamydia compared with non-Indigenous people,24 and prevalence has been found to be higher in non-residents compared with Australian residents in sexual health services due to higher risk-taking behaviour 25…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, backpackers are more likely to take part in adventure sports and other high-risk behavior, such as drinking alcohol to hazardous levels. 10 Therefore, they may be more likely to be involved in accidents than people traveling as part of an organized tour group or for business purposes. 2 Coping with health issues is more complicated for travelers with underlying medical conditions.…”
mentioning
confidence: 99%